Remodeling characteristics and collagen distribution in biological scaffold materials explanted from human subjects after abdominal soft tissue reconstruction: an analysis of scaffold remodeling characteristics by patient risk factors and surgical site classifications - Cavallo, Jaime A; Roma, Andres A; Jasielec, Mateusz S; Ousley, Jenny; Creamer, Jennifer; Pichert, Matthew D; Baalman, Sara; Frisella, Margaret M; Matthews, Brent D; Deeken, Corey R (Annals of surgery, 2015)
The study purpose was to evaluate the associations between patient characteristics or surgical site classifications and the histologic remodeling scores of biologic meshes biopsied from abdominal soft tissue repair sites in the first attempt to generate a multivariable risk-prediction model of nonconstructive remodeling. Host characteristics and surgical site assessments may predict remodeling degree for biologic meshes used to reinforce abdominal tissue repair sites. Biologic meshes were biopsied from the abdominal tissue repair sites of n = 40 patients during an abdominal reexploration, stained with hematoxylin and eosin, and evaluated according to a semi-quantitative scoring system for remodeling characteristics (cell types, cell infiltration, extracellular matrix deposition, scaffold degradation, fibrous encapsulation, and neovascularization) and a mean composite score. Biopsies were stained with Sirius Red and Fast Green and analyzed to determine the collagen I:III ratio. On the basis of univariate analyses between subject clinical characteristics or surgical site classification and the histologic remodeling scores, cohort variables were selected for multivariable regression models using P ≤ 0.200. The model selection process for cell infiltration score yielded 2 variables: age at mesh implantation and mesh classification (C statistic = 0.989). For the mean composite score, the model selection process yielded 2 variables: age at mesh implantation and mesh classification (r = 0.449). These preliminary results constitute the first steps in generating a risk-prediction model that predicts the patients and clinical circumstances most likely to experience nonconstructive remodeling of abdominal tissue repair sites with biologic mesh reinforcement.